Effect of Travel Time for Thyroid Surgery on Treatment Cost and Morbidity. Issue 9 (September 2019) - Ramirez, Adriana G.; Schneider, Eric B.; Mehaffey, J. Hunter; Zeiger, Martha A.; Hanks, John B.; Smith, Philip W.
Regionalizing surgical care to high-volume centers has improved outcomes for endocrine surgery. This shift is associated with increased travel time, costs, and morbidity within certain patient populations. We examined travel time–related differences in demographics, health-care utilization, thyroid-specific disease, and cost for patients undergoing thyroid surgery at a single high-volume center. Data were extracted from the 2005 to 2014 ACS-NSQIP and clinical data repository for patients undergoing thyroid surgery. Travel times between patients' home address and the hospital were calculated using Google Earth under assumptions of standard road conditions and speed restrictions. Travel time was divided into <2 hours versus ≥2 hours. Primary outcomes were hospital cost and 30-day morbidity. Factors associated with travel time and primary outcomes were analyzed using appropriate bivariate tests and multivariable regression modeling. A total of 1046 thyroid procedures were included, with median (IQR) travel time of 68.8 (40.1–107.2) minutes. Eight hundred forty-seven (80.9%) patients traveled <2 hours compared with 199 (19.1%) traveled ≥2 hours. Patients traveling ≥2 hours were more likely to have complex thyroid disease (37.7% vs 27.6%, P = 0.005), uninsured status (31.1% vs 11.8%, P < 0.001), lower preoperative morbidity risk (2.3% vs 2.7%, P = 0.02), and longer length of stay (1.21 vs 1.07 days, P = 0.04), but similar median operative times (163 vs 165 minutes, P = 0.89). Average cost was higher for patients traveling ≥2 hours (7300 vs 6846 [2014 USD], P = 0.05). Despite observed patient differences, hospital costs and postoperative morbidity did not differ after adjustment. Existing management practices and the nature of the disease process may be protective against the potential negative effects of regionalization.